Evolution of Modeling for Lightweight Structures: Creating the Munich Olympic Stadium Roof (1967–72). Issue 2 (3rd July 2022) - Whitehead, Rob
Abstract : The experimental structural qualities of the Munich Olympic Stadium roof compelled formative innovations in modeling techniques responsive to those conditions. The novel use of large-scale physical models allowed the team to navigate the complicated nature of generative form-finding for lightweight structures by balancing the various parameters of forms and forces. Although physical modeling was initially beneficial, it became obsolete as refinement and confirmation became requisite. The cable-net structure exceeded conventional capacity for analysis, which drove the engineers to evolve their confirmative modeling methods. Instead of abandoning the parametric logic of these physical models, the design team embraced this approach and applied their complementary interdisciplinary expertise to create two groundbreaking computational modeling techniques that are still in use today. Their modeling techniques exceeded their mandate for simple confirmation and evolved into the first generative and optimizing parametric modeling options for lightweight structures. The findings will show how the evolving use of these models and the collaborative complications that ensued situate contemporary challenges of experimental design, technology, and practice.